Studi Eksplorasi Desain Rumah Prafabrikasi Berdasarkan Bentuk Modul Komponen sebagai Alternatif Desain Rumah Sederhana - Anjar Primasetra (Institut Teknologi Sains Bandung, 2020)
The needs for rapid housing construction has become a very important issue nowadays because of very high housing backlog. Housing construction in the community still use conventional construction systems that have many weaknesses, one of it weakness is the problem of delays in construction time that often occurs due to project managerial problems and poor HR capacity. One alternative for accelerating development is the usage of prefabrication method. Prefabrication method allows the creation of a system to speed up the house building construction is commonly called a prefabricated house. The prefabrication industry in Indonesia is less rapidly developing because its components tend to have rigid designs that make it unattractive, and the costs are relatively more expensive when compared to conventional house. There are four types that includes in prefabricated houses that have been known before, they are RISHA, RUMANAGA, DOMUS, and DUBLDOM. The four prefabricated houses have been assessed in terms of building components and design through industrial research and development. This research is aimed to conduct a study of exploration of prefabricated house design by evaluating the weaknesses of prefabricated houses, especially in terms of module shape and components. In addition, it also examines the minimum size of house area needed in fulfilling the size of a modest house according to a literature study from previous research. From the evaluation results, the prefabricated house design is then formulated in several design alternatives to look for the possibility designs that can be developed. From the results of the study, the size of the module developed to explore the design is to use modules with multiples of 30 cm with a minimum size of the module is 2.4 m x 2.4 m and the maximum size of the module is 3 m x 3 m. Meanwhile, for the area of the house building that was developed there were three alternatives area of the house chosen, they are: small type (28.8 m2), medium type (36 m2), large type (43.2 m2) with minimal house needs, they are: gathering space (living room/room family/kitchen), bedroom, service room (bathroom), and terrace. It is expected that the results of design exploration will be an alternative design for the development of simple home designs.